Mooi Indie Paintings: The Antagonism and Its Politicality - Harfiyah Widiawati; Aris Masruri Harahap; Lambok Hermanto Sihombing (Jurusan Sastra Indonesia, 2020)
For some people, Indonesia during colonial period is often imagined as a beautiful, quiet, peaceful, and harmonious country. Such imagination, for example, resides in the concept of Mooi Indie paintings which emerged out of Indonesian history during the Dutch colonial period. However, for other people, such representations were opposed because they were merely romanticized representation by painters patronized by the Dutch colonials who wanted to romanticize the memory of their past in East Indies. In this article, we discussed how the concept of Mooi Indie appears in certain Indonesian landscape paintings, how the antagonism comes into sight, and how its politicality works.